2018
DOI: 10.1111/jcmm.13724
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK/Fn14 mediates atrial‐derived HL‐1 myocytes hypertrophy via JAK2/STAT3 signalling pathway

Abstract: Atrial myocyte hypertrophy is one of the most important substrates in the development of atrial fibrillation (AF). The TWEAK/Fn14 axis is a positive regulator of cardiac hypertrophy in cardiomyopathy. This study therefore investigated the effects of Fn14 on atrial hypertrophy and underlying cellular mechanisms using HL‐1 atrial myocytes. In patients with AF, Fn14 protein levels were higher in atrial myocytes from atrial appendages, and expression of TWEAK was increased in peripheral blood mononuclear cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Tnfrsf12a also known as TWEAKR/FN14 is expressed at low basal levels in the heart ( 98 ) and sustained expression of the receptor results in adverse cardiac fibrotic remodeling and heart failure as a result of sensitized inflammatory response ( 99 ). Indeed, cardiac hypertrophy due to increased fibroblast proliferation downstream of increased TWEAKR activity is supported by JAK2/STAT3 mediated hypertrophy in atrial myocytes ( 100 ). Hbegf encodes heparin-binding extracellular growth factor protein which increase AKT activity, cardiac fibroblast proliferation and secretion of Type 1 collagen to influence cardiac remodeling, stiffness and contractility ( 101 ) which could have an additive effect with overexpressed TWEAKR discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Tnfrsf12a also known as TWEAKR/FN14 is expressed at low basal levels in the heart ( 98 ) and sustained expression of the receptor results in adverse cardiac fibrotic remodeling and heart failure as a result of sensitized inflammatory response ( 99 ). Indeed, cardiac hypertrophy due to increased fibroblast proliferation downstream of increased TWEAKR activity is supported by JAK2/STAT3 mediated hypertrophy in atrial myocytes ( 100 ). Hbegf encodes heparin-binding extracellular growth factor protein which increase AKT activity, cardiac fibroblast proliferation and secretion of Type 1 collagen to influence cardiac remodeling, stiffness and contractility ( 101 ) which could have an additive effect with overexpressed TWEAKR discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial myocyte hypertrophy plays an essential role in AF. In this sense, Fn14 protein expression is increased in atrial appendages from patients with AF compared with normal subjects [99]. In addition, TWEAK protein expression is elevated in peripheral blood mononuclear cells from patients with AF.…”
Section: Tweak and Heart Failurementioning
confidence: 95%
“…In the same way, it has been demonstrated that incubation of atrial myocytes (HL-1) with rTWEAK induces hypertrophy on these cells. TWEAK-induced myocytes hypertrophy is associated with JAK2/STAT3 pathway activation since Fn14-specific siRNA decreases JAK2/STAT3 activation and hypertrophy of atrial myocytes [99].…”
Section: Tweak and Heart Failurementioning
confidence: 98%
“…TWEAK–Fn14 axis has shown an increasingly important role in cardio-cerebral vascular diseases (Blanco-Colio, 2014). The interaction of TWEAK and Fn14 activates downstream signaling processes during disease development and progression, which includes mediating atrial-derived HL-1 myocytes hypertrophy via the JAK2/STAT3 signaling pathway (Hao et al, 2018), weakening the antiproliferative effects of miR-149 in osteosarcoma via the AKT serine/threonine kinase (PI3K/AKT) signaling pathway (Xu et al, 2018), inducing pro-fibrotic responses leading to heart failure via the NF-κB and/or AP-1 signaling pathway (Das et al, 2018), preventing renal damage in patients with lupus nephritis via type I interferon signaling pathway (Xue et al, 2017), and promoting wound healing processes through favoring regional inflammation, cytokine production, and extracellular matrix synthesis (Liu et al, 2018). In addition, TWEAK also participates in a variety of other diseases such as tumors (Hu et al, 2017), neonatal hypoxia–ischemia (Kichev et al, 2018), human glioma (Guan et al, 2017), psoriasis (Sidler et al, 2017), and chronic colitis (Son et al, 2013).…”
Section: Introductionmentioning
confidence: 99%